High levels of circulating osteopontin in inflammatory lung disease regardless of Sars‐CoV‐2 infection - Giuseppe Cappellano; Hugo Abreu; Davide Raineri; Lorenza Scotti; Luigi Castello; Rosanna Vaschetto; Annalisa Chiocchetti (EMBO Molecular Medicine, 2021)
Graphical Abstract This study independently confirms increased levels of osteopontin in COVID‐19 patients but also suggests that osteopontin cannot be used as a biomarker of SARS‐CoV‐2 infection, as elevated levels of circulating osteopontin are found in inflammatory lung disease regardless of SARS‐CoV‐2 infection.